Research on Middle School Chemistry Teaching Design Based on Real Problem Situation - Wu, Liming; Zhang, Xinyu; Sun, Lin (Advances in Social Sciences Research Journal, 2024)
In today’s society, education in our country is showing an increasing trend of development. Chemistry, as a subject, has also made great progress. Most of the chemistry teaching models we remember from our childhood are to instil concepts, memorize concepts and ignore the combination of concepts with real-life situations, resulting in a mechanized and monotonous approach to learning chemistry. As a result, most secondary school students are not very good at chemistry. The reason for this is that chemistry is a very logical subject, and a large amount of chemical knowledge can be memorized by students using only one-sided words, which is still a challenge for them to understand. However, interest is the most valuable asset of children, therefore, this paper will be based on the existing information, and combined with the current theoretical research and development trend, in-depth discussion of the importance of the problem contextualized chemistry teaching, and through practical cases to explore how to better integrate the problem context into the chemistry classroom.